Structural properties of supercooled deep eutectic solvents: choline chloride–thiourea compared to reline. Issue 10 (24th February 2022) - Golysheva, Elena A.; Maslennikova, Natalya A.; Baranov, Denis S.; Dzuba, Sergei A.
Abstract : Deep eutectic solvents (DESs) are eutectic mixtures of hydrogen bond acceptors and hydrogen bond donors which melt at much lower temperatures than the individual components. Abstract : Deep eutectic solvents (DESs) are eutectic mixtures of hydrogen bond acceptors and hydrogen bond donors which melt at much lower temperatures than the individual components. DESs are attracting growing interest because of a large variety of possible technological applications. Here, supercooled DESs consisting of choline chloride–urea (1 : 2) (reline) and of choline chloride–thiourea (1 : 2) (ChCl–thiourea), with introduced nitroxide spin probe tempone, were studied by electron paramagnetic resonance (EPR) spectroscopy. Conventional continuous wave (CW) EPR spectra showed the coexistence of solid and liquid microphases, with microviscosity of ∼ 10 P in the latter case. CW EPR spectra taken at different temperatures for ChCl–thiourea showed isosbestic points, which indicates that two phases are separated by sharp boundaries; for reline these points are rather diffuse, which in turn implies diffuse boundaries. Stochastic molecular librations detected by pulsed EPR possess the ability for elucidating nanoscale features of molecular packing; the data obtained showed a drastic difference for the onset of these motions for ChCl–thiourea and for reline, which was interpreted as evidence that the rigidity of molecular packing for ChCl–thiourea is stronger than that for reline. The temperature dependence of stochastic molecular librations for reline was found to be similar to that known for lipid bilayers and globular proteins, which indicates the proximity of the characteristics of molecular packing in these molecular systems.